Analisis Kesejahteraan Petani Tembakau Pamekasan dalam Perspektif Ekonomi Pembangunan - Ach Saifullah; Asyari Asyari; Mahalli Andriyanto; Farahdilla kutsiyah (Yayasan Cendekia Gagayunan Indonesia, 2025)
The paradox of the development of the tobacco sector in Pamekasan Regency can be seen from the increase in planting area and productivity from 22.3 thousand hectares in 2023 to 31.1 thousand hectares in 2024 which is not directly proportional to the welfare of farmers. This study aims to analyze the structural and cultural roots that cause asynchrony between production growth and welfare improvement. Using qualitative methods with case study designs, data were collected through in-depth interviews, field observations in four tobacco center villages, and document analysis. The data was analyzed thematically by combining the Agrarian Political Economy framework, Welfare Theory, and Sustainable Livelihood Framework (SLF). The results of the study show that inequality in the political economy structure including the dominance of middlemen, weak bargaining positions of farmers, ineffective allocation of DBHCHT, and distortion of access to production inputs are the main causes of welfare stagnation. In addition, local cultural factors create a cultural lock-in that reinforces farmers' systemic dependence on traditional marketing networks. These findings indicate the need for policy reforms that are transformative, targeted, and sensitive to socio-cultural dynamics in order to improve the welfare of tobacco farmers in a sustainable manner.